Influence of Digital Literacy on Democratic Participation among Secondary School Students in Gusau Educational Zone, Zamfara State - Sule Muhammad; Zulyadaini Sani Gaya (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study examined the influence of digital literacy on democratic participation among secondary school students in the Gusau Educational Zone, Zamfara State. Anchored on Ribble’s (2008) Digital Citizenship Theory, the research adopted a descriptive correlation design, targeting 8,753 SS2 students across Gusau and Tsafe Local Government Areas. A stratified random sample of 365 students was selected, and data were collected using a validated questionnaire measuring digital literacy competencies and democratic engagement. Analyses included one-sample t-tests to assess the levels of digital literacy and democratic participation, and simple linear regression to determine the influence of digital literacy on democratic participation. Results indicated that students possessed moderate to high digital literacy (M = 3.41, SD = 0.72), actively engaged in democratic processes (M = 3.18, SD = 0.69), and that digital literacy significantly predicted democratic participation (β = 0.62, p < .001). Findings underscore that competence in accessing, evaluating, and using digital tools empowers students to participate meaningfully in civic and school-related activities. The study recommends structured digital literacy programs, integration of digital tools into civic education, teacher training, and equitable access to digital resources to enhance participatory citizenship among secondary school students.